Double-Crop Sunflower Cost-Return Budget in North Central and Eastern Kansas - Fogleman, Sarah L.; Lubben, Bradley D. (My University, 2000)
This publication provides estimated cost and returns for forward farm planning for a double-crop sunflower production system in north central and northeastern Kansas.
MF2145_2000_10
Keywords: MF2145; Crops; Economics; MF